2005
DOI: 10.1007/s11248-004-7435-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of EPA and DHA biosynthesis by over-expression of masu salmon Δ6-desaturase-like gene in zebrafish

Abstract: The n - 3 polyunsaturated fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have important nutritional benefits in humans. Farmed fish could serve as promising sources of EPA/DHA, but they need these fatty acids or their precursors in their diets. Here we transferred masu salmon delta6-desaturase-like gene in zebrafish to increase its ability for synthesizing EPA and DHA. Expression of this gene in transgenic fish elevated their EPA content by 1.4-fold and DHA by 2.1-fold. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 32 publications
1
30
1
5
Order By: Relevance
“…There have also been research studies in fish specifically targeting LC-PUFA metabolism. Transgenic zebrafish (Danio rerio) have been produced by transformation with Δ6 and Δ5 fatty acyl desaturases of masu salmon (Oncorhynchus masou) (Alimuddin et al, 2005(Alimuddin et al, , 2007, and both zebrafish (Alimuddin et al, 2008) and the marine teleost, nibe croaker Nibea mitsukurii (Kabeya et al, 2014), have been transformed with fatty acid elongase from masu salmon. Recently, the production of n-3 PUFA, specifically LNA from 18:1n-9, was demonstrated in GM-zebrafish transformed with fat-1 and fat-2 genes (Pang et al, 2014).…”
Section: Enhancing Endogenous Lc-pufa Production and Retentionmentioning
confidence: 99%
“…There have also been research studies in fish specifically targeting LC-PUFA metabolism. Transgenic zebrafish (Danio rerio) have been produced by transformation with Δ6 and Δ5 fatty acyl desaturases of masu salmon (Oncorhynchus masou) (Alimuddin et al, 2005(Alimuddin et al, , 2007, and both zebrafish (Alimuddin et al, 2008) and the marine teleost, nibe croaker Nibea mitsukurii (Kabeya et al, 2014), have been transformed with fatty acid elongase from masu salmon. Recently, the production of n-3 PUFA, specifically LNA from 18:1n-9, was demonstrated in GM-zebrafish transformed with fat-1 and fat-2 genes (Pang et al, 2014).…”
Section: Enhancing Endogenous Lc-pufa Production and Retentionmentioning
confidence: 99%
“…Chemical analysis showed that the muscles of transgenic fish contained considerably higher levels of EPA and DHA compared with control fish (Alimuddin et al, 2008). Summing up the findings of this series of model studies, it ought to be stressed that masu salmon desaturases and elongase transgenes were functional in zebrafish and were able to beneficially alter the species' fatty-acid metabolic pathway, suggesting that this technology might be used to modify farmed fish to produce nutritionally improved, healthy meat for human consumption (Alimuddin et al, 2005(Alimuddin et al, , 2007(Alimuddin et al, and 2008.…”
Section: Modifications Of the Composition Of Milk Lipidsmentioning
confidence: 88%
“…Overexpression of this transgene in modified zebrafish highly elevated body EPA (by a factor of 1.4) and DHA concentrations (by a factor of 2.1). Simultaneously, the content of ALA, being a substrate of Δ6 desaturase, decreased, while total lipids were not changed (Alimuddin et al, 2005). The authors indicated that their results demonstrated the possibility of beneficial modification of the fatty-acid metabolic pathway in fish through the transgenic technique.…”
Section: Modifications Of the Composition Of Milk Lipidsmentioning
confidence: 91%
See 1 more Smart Citation
“…Total lipid was extracted from a pool of 3-4 adults in triplicate for each transgenic and non-transgenic sibling using the chloroform-methanol (2:1) method as described by Folch et al (1957). Fatty acid methyl esters were prepared and analyzed by gas liquid chromatography as described by Alimuddin et al (2005).…”
Section: Analysis Of Epa/dha Contentmentioning
confidence: 99%